A Systematic Review of the Impact of Diabetes Resilience on Quality of Life - Arifin, Hidayat; Kusnanto, Kusnanto; Widyawati, Ika Yuni (International Journal of Psychosocial Rehabilitation, 2020)
Patients who have regular treatments and who stick to the recommended diet for diabetes mellitus (DM) will cause a burnout in undergoing treatment. This will make their blood sugar level unstable and result in incomplete treatment. The present study aimed to analyze the diabetes resilience related to quality of life (QoL) using a systematic review. This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The subject was extensively searched for in the Scopus, Science Direct and CinaHl databases. The search utilized the phrases “resilience,” “resilient,” “resiliency,” “Quality of Life,” and “diabetes mellitus.” The search was conducted focused on the titles, abstracts and keywords. The inclusion criteria in the study literature were that the document type was an original article, that the source was a journal, that the article was written in English and that the full text was available. The age of the subject in the items was not specified to capture the resilience in type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) as broadly as possible. The publication time limit was 2014 to 2019. We identified 270 articles where 15 were considered relevant for this systematic review. The results showed that the patients would have a better quality of life after entering a resilient condition while undergoing diabetes treatment. The present review study suggests that optimizing diabetes resilience will influence the quality of life of DM patients. Nurses and other health care professions should consider ways to improve resilience.